The Effect of Education and Religion in Early Childhood on Social Coexistence and Tolerance: A Case Study of Fifth and Sixth Grade Students in Damascus Governorate (The International Journal of Educational Sciences and Arts, 2023)
The study aimed to reveal the effect of education and religion in early childhood on coexistence and societal tolerance as estimated by fifth and sixth grade students in Damascus governorate schools, and to measure the differences between the average scores of the research sample's responses to the societal tolerance scale according to the variables of gender and grade; The current research adopted the descriptive analytical approach, applied the measure of societal tolerance, and the research sample included (294) boys and girls. Among the most important results of the research: The level of influence of education and religion in early childhood on coexistence and societal tolerance according to the estimation of fifth and sixth grade students in Damascus governorate schools was average with a degree of (3.30). The grade variable is in favor of children in the sixth grade.
Keywords: Education; Religion; Early Childhood; Coexistence; Societal Tolerance